Bacterioplankton community diversity of a portuguese aquifer system (Maciço Calcário Estremenho) - Figueiredo, Daniela R. de (2024)
Climate change may increase the vulnerability of aquifers to contamination through extreme precipitation and extended drought periods. Therefore, the understanding of groundwater ecosystem dynamics is crucial, with bacterial assemblages playing a major role in biogeochemical cycles. The present research describes a geospatial study targeting the bacterial community structure of groundwaters from the largest karst aquifer in Portugal (the Maciço Calcário Estremenho), integrating hydrogeochemical and bacterial diversity data. A total of 22 samples were analyzed from a set of 11 geographically sparsely distributed groundwater sources in dry vs. wet seasons. The 16S rRNA gene barcoding data revealed bacterial community variability across samples in space and time. The phylum Proteobacteria was dominant across all samples (from 44 to 92% of total sequence reads), mainly represented by the classes Alphaproteobacteria (orders Sphingomonadales, BD7–3, Rhizobiales and Rhodospirillales), Betaproteobacteria (orders Burkholderiales, Rhodocyclales, Nitrosomonadales), Gammaproteobacteria (orders Pseudomonadales, Xanthomonadales, Alteromonadales, Legionellales) and Deltaproteobacteria (orders Myxococcales, Spirobacillales). Variation in the bacterial community was primarily attributed to parameters such as redox conditions (DO, ORP), Fe, Mn, SO4, PO4, Sr and Cl, but also some minor and trace elements (Al, V, Cr, Cu, Pb). Our results provide novel insights into bacterial diversity in relation to groundwater hydrogeochemistry. The strong dominance of OTUs related to bacterial taxa associated with nitrification/denitrification also highlights a potentially important role of these assemblages on nutrients (nitrogen sources) and groundwater quality dynamics at this karstic aquifer system. Moreover, the integration of bacterial assemblages information is emphasized as central for water quality monitoring programs.